EVALUASI KINERJA GRATE COOLER PADA UNIT CLINKER COOLER PADA PT SEMEN BATURAJA Tbk. - Kurnia, Indah; Safaruddin, Safaruddin; Haykal, Ahmad (Jurnal Multidisipliner Bharasumba, 2023)
The grate cooler is one of the important tools in the cement-making process because apart from cooling the clinker to obtain the appropriate clinker quality, the garage cooler also serves to provide hot air for burning coal in the clinker and calciner as well as hot air for drying raw materials and coal. Grate coolers have functions that other types of coolers do not have, namely Planetary Coolers and Rotary Coolers. Therefore it is necessary to know the properties of the Grate Cooler so that it can be operated optimally in supporting the clinical performance of the system. In the clinker cooling process in the Grate Cooler, the quenching process usually occurs at a distance of the first 5 meters. In this quenching process, the need for cooling air for grate expansion is higher compared to other cooling processes. The quenching process which causes a rapid decrease in clinker temperature has an impact on the availability of air at very high temperatures between 1200oC-1400oC. This high temperature air must be used properly to be useful for the combustion process in Kilns and Kalsiner.